Aesthetic Concepts - Sibley, Frank N. (Sociologija. Mintis ir veiksmas, 2001)
Translation: Sibley, Frank N. “A Contemporary Theory of Aesthetic Concepts” in G. Dickie, R. Sclafani (eds.). 1977. Aesthetics: A Critical Anthology. New York: St. Martins Press. Translated by Vygandas Aleksandravičius; edited by Antanas Katalynas.